Tofacitinib modulates the VZV-specific CD4+ T cell immune response in vitro in lymphocytes of patients with rheumatoid arthritis. (18th May 2019) - Almanzar, Giovanni; Kienle, Felix; Schmalzing, Marc; Maas, Anna; Tony, Hans-Peter; Prelog, Martina
Abstract: Objective: RA is a chronic inflammatory disease characterized by lymphocyte infiltration and release of inflammatory cytokines. Previous studies have shown that treatment with Janus kinase inhibitors, such as tofacitinib, increased the incidence rate of herpes zoster compared with conventional DMARDs. Therefore, this study aimed to investigate the effect of tofacitinib on the varicella-zoster-virus (VZV)-specific T cell immune response. Methods: The effect of tofacitinib on the VZV-specific T cell immune response was determined by evaluating the IFNγ production, the proliferative capacity, the VZV-induced differentiation into effector and memory T cells, the expression of activation marker CD69 and helper T cell type 1 (Th1)-characteristic chemokine receptors, such as CXCR3 and CCR5, as well as cytotoxic activity (perforin and granzyme B expression) of CD4 + T cells of patients with RA compared with healthy donors upon stimulation with VZV antigen in vitro . Results: Tofacitinib significantly reduced the IFNγ production, proliferation, activation, and CXCR3 expression of VZV-specific CD4 + T cells in a dose-dependent manner in short- and long-term lymphocyte culture. No effect on the distribution of naive, effectors or memory, or on the expression of perforin or granzyme B by VZV-specific CD4 + T cells was observed. Conclusion: This study showed that tofacitinib significantly modulated the Th1 response to VZV. The poor VZV-specific cellular immune response in patients with RA may be considered in recommendations regarding appropriate vaccination strategies for enhancing the VZV-specific Th1 response.